8 Formal reporting of paediatric electrocardiograms in a tertiary paediatric cardiology centre. (2nd February 2018) - Bannerman, K; Ferguson, R; Abumehdi, MR
Abstract : Purpose: To review indications for and results of ECGs undertaken outwith the cardiology department and recommendations made by reporting cardiology physicians. Methods: A single centre retrospective study of all ECGs reported between May and July 2017 in a large children's hospital. Indication for ECG, reporting cardiologist's opinion and management plan were assessed. Results: 139 ECGs were reported. 89.9% of patients required no further action on the basis of their ECG report. 5% were referred for cardiology review and for 4.3% further clinical information or 'clinical correlation' was requested. Repeat ECG was requested once. The most common indication for ECG was 'collapse' (28.1%). Of these, 87.2% of these required no further follow-up and 5.1% were referred to cardiology. 27 ECGs were performed for QT-prolonging medications of which 88.5% did not warrant further review, 7.7% were referred to cardiology. 17 ECGs were performed for chest pain but 93.8% required no follow-up. 38 ECGs (27.3%) were undertaken for other indications (e.g. hearing loss, ectopics, murmur, eating disorders.) 89.5% of these needed no follow-up and 5.3% were referred to cardiology. Conclusion: ECGs are a common first line investigation in the acute and outpatient setting. The majority of these are found to be normal, even when cardiology referral is required. It is rare that significant cardiac pathology is diagnosed. Collapse, the most common indication for ECG, again demonstrated a low positive yield. We have demonstrated that although a commonly used investigation, the majority are normal and that ECG abnormalities are an uncommon presentation of cardiac disease in children.